Positive and negative effects of a company’s relationships in the internationalization process - Ratajczak-Mrozek, Milena; Mielcarek, Paweł (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The main purpose of this article is to propose a conceptual framework combining both the scope and strength of a company’s relationships thereby allowing it to achieve better results in terms of the effects accompanying the company’s internationalisation. We propose a conceptual model of four types of relationships in the internationalisation process. We call them: domestic contacts, domestic embeddedness, international exploration and international exploitation, as internationalisation does not mean that a company gives up contacts with domestic entities at the same time. These types of relationships generate positive and negative effects depending on the scope of the relationship (domestic/international) and its strength (weak/strong). By looking at internationalisation from the complex perspective of both domestic and foreign relationships, we point to the need for a comprehensive look at the internationalisation process, its accompanying effects and the related problems of relationship management. To achieve this purpose we primarily adopt the network model of internationalisation and integrate it with the strategic approach to network analysis. Our proposal allows us to analyse the effects of interdependencies in a global business landscape including the conditions under which relationships management and internationalisation lead to improved performance
Argumenta Oeconomica, 2017, Nr 1 (38), s. 121-144
Keywords: internationalisation; network model of internationalisation; relationship strength; relationship management; internationalisation effects; company performance